(Debt) Overhang: Evidence from Resource Extraction. (12th June 2020) - Wittry, Michael D
Abstract: I study the empirical importance of debt overhang using a unique data set on resource extraction firms that provides ex ante measures of investment opportunities and important variation in terms of a firm's obligations. In particular, unsecured reclamation liabilities create overhang that is costly to resolve and induces firms to forgo and postpone positive NPV investments. Traditional debt, in contrast, imposes few overhang-related investment distortions. These results show that (a) the overhang problem is potentially large and more broadly applies to firms' nondebt liabilities and (b) overhang problems associated with traditional debt can be avoided through contracting and debt composition.